An RNA aptamer to HP1/Swi6 facilitates heterochromatin formation at an ectopic locus in S.pombe. Issue 6 (3rd June 2019) - Rani, Rita; Yaseen, Abdul Mohd.; Malwade, Akshay; Sevilimedu, Aarti
ABSTRACT: In the fission yeast Schizosaccharomyces pombe (S. pombe ), heterochromatin domains are established and maintained by protein complexes that contain numerous RNA binding domains among their components. The fission yeast HP1 protein Swi6 is one such component and contains an unstructured RNA-binding hinge, which is important for the integrity and silencing of heterochromatin. In this study, we have used an RNA aptamer that likely binds to the Swi6 hinge with high affinity, as a tool to perturb the natural interactions mediated by this domain. When the hinge is blocked by the aptamer RNA, Swi6 appears to become less restricted to the pericentromeres and is enriched at specific euchromatic loci. This suggests a role for the Swi6 hinge, along with the chromoshadow domain (previously shown) in controlling the spread of heterochromatin in S.pombe . The study also highlights the potential of using a synthetic aptamer RNA as a tool to perturb nucleic acid – protein interaction in vivo with the objective of understanding the functional relevance of such an interaction.